Organizational creativity strategy and strategic partnership in improving positional advantage of vocational high schools in west java - Sundusiah, Sundusiah; Rahayu, Agus; Disman, Disman; Suryadi, Edi; Ramdhany, Muhamad Arief (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to examine the role of organizational creativity strategies in improving positional advantage in Vocational High Schools (SMK) Centers of Excellence in West Java, by considering the influence of Organizational Creativity and Partnership Program. This study uses a quantitative approach with a data collection tool in the form of a questionnaire distributed to 165 schools from a total of 288 SMK Centers of Excellence in West Java. Sampling was carried out using a stratified random sampling technique. Data were analyzed using the Partial Least Squares (PLS) method, using a Likert measurement scale to assess the variables in the study. The results showed that Organizational Creativity and Partnership Program had a significant influence on positional advantage, with Partnership Program having a greater impact. The main finding of this study is the importance of strengthening organizational creativity in dealing with the dynamics of the external and internal environments of schools. The novelty of this study lies in the integration of two factors Organizational Creativity and Partnership Program—in developing positional advantage in SMK, which has not been widely discussed in previous literature.